Endoscopic banding without resection (BWR) technique for treatment of diminutive neuroendocrine tumors in the duodenum - Khara, Harshit S.; Shovlin, Gerald J.; Johal, Amitpal S.; Diehl, David L. (Endoscopy International Open, 2019)
Endoscopic treatment of diminutive (less than 10 mm) duodenal neuroendocrine tumors (NETs) is recommended because of the risk of metastatic potential. Endoscopic mucosal resection and endoscopic submucosal dissection are alternatives to surgical management but have significant adverse event rates. We evaluated the effectiveness, feasibility, and safety of the ‘banding without resection’ (BWR) technique and assessed outcomes for the treatment of diminutive duodenal NETs. Our study included eight patients referred for endoscopic treatment of incidentally discovered, biopsy proven, diminutive duodenal bulb NETs. Endoscopic ultrasound (EUS) in all patients showed duodenal bulb NETs located in the deep mucosa and submucosal layers without any nodal metastasis. The BWR technique was successfully performed in all patients with technical feasibility, with the assistance of submucosal saline lift in three patients when the lesion was smaller than 5 mm in size, without any immediate or delayed adverse events. Complete resection with no residual lesion was confirmed at short-term (median 2.3 months) and long-term (median 4.2 years) follow-up intervals by repeat endoscopy, biopsy, and EUS exam. The BWR technique appears to be a safe, feasible, and effective therapy for endoscopic treatment of diminutive duodenal bulb NETs in the absence of local and distant metastasis.